BEYOND WORDS: ANALYZING HAIKU TEACHING DISCOURSE AND ITS IMPACT ON PRACTICE - Grayson Cloutier (European International Journal of Pedagogics, 2024)
This study explores the discourse surrounding the teaching of haiku, focusing on the transition from verbal discussion to practical application in the classroom. By employing a qualitative analysis of classroom interactions, instructional materials, and educator reflections, the research investigates how the discourse shapes both teaching practices and students' engagement with haiku writing. The findings reveal that while discussions about haiku often emphasize structure and themes, the actual practice of writing haiku involves a deeper exploration of sensory experience and emotional expression. Additionally, the analysis highlights the role of feedback and collaborative learning in enhancing students' understanding and appreciation of haiku as a poetic form. Ultimately, this study underscores the importance of bridging the gap between theoretical discussions and practical application, offering insights for educators to foster a more experiential and meaningful haiku writing process in their classrooms.